2012
DOI: 10.1113/expphysiol.2011.061580
|View full text |Cite
|
Sign up to set email alerts
|

Na+ transport across rumen epithelium of hay‐fed sheep is acutely stimulated by the peptide IGF‐1 in vitro

Abstract: An energy-rich diet leads to enhanced ruminal Na(+) absorption, which is associated with elevated plasma insulin-like growth factor 1 (IGF-1) levels and an increased number of IGF-1 receptors in rumen papillae. This study examined the in vitro effect of IGF-1 on Na(+) transport across the rumen epithelium of hay-fed sheep, in which the IGF-1 concentration in plasma is lower than in concentrate-fed animals. At concentrations ranging from 20 to 100 μg l(-1), serosal LR3-IGF-1, a recombinant analogue of IGF-1, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…Several factors influence Na ϩ transport, including luminal osmolality (49), SCFA concentration (52), and, more recently, it has been demonstrated that IGF-1 acutely stimulates Na ϩ transport (53). However, in the current study, mRNA abundance of IGFBP5 was downregulated, and IGFBP3 was not affected by increasing days fed the moderate-grain diet.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Several factors influence Na ϩ transport, including luminal osmolality (49), SCFA concentration (52), and, more recently, it has been demonstrated that IGF-1 acutely stimulates Na ϩ transport (53). However, in the current study, mRNA abundance of IGFBP5 was downregulated, and IGFBP3 was not affected by increasing days fed the moderate-grain diet.…”
Section: Discussioncontrasting
confidence: 64%
“…However, in the current study, mRNA abundance of IGFBP5 was downregulated, and IGFBP3 was not affected by increasing days fed the moderate-grain diet. Although these receptors influence epithelial growth (18,54), IGF also acutely stimulates Na ϩ absorption in the rumen (53). This opposes results previously showing upregulation of IGFBP5 within 1 wk of abrupt grain adaptation in mature nonlactating dairy cows (55), and as early as 4 days after inducing a grain challenge in second-lactation dairy cows (56).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Recent studies also point to the impact of butyrate on the activity of the endocrine system. The increase in the concentrations of gastrin, secretin, cholecystokinin, glucagon-like peptide 2, and IGF-1 in the blood and the increase in IGF-receptor 1 in the ruminal epithelial cells have been observed as a result of butyrate supplementation (Shen et al, 2005;Gorka et al, 2009;Guilloteau et al, 2010;Kato et al, 2011;Shen et al, 2012). All of these proteins and peptides are considered hormonal signals that regulate the nutrient absorption, metabolism and growth in mammalian tissues (Shen et al, 2004;Siddle, 2011;Connor et al, 2015).…”
Section: Exogenous Butyrate In Calf Rearingmentioning
confidence: 99%